2020
DOI: 10.1016/j.eclinm.2020.100553
|View full text |Cite
|
Sign up to set email alerts
|

Sarilumab use in severe SARS-CoV-2 pneumonia

Abstract: Background Interleukin-6 signal blockade showed preliminary beneficial effects in treating inflammatory response against SARS-CoV-2 leading to severe respiratory distress. Herein we describe the outcomes of off-label intravenous use of Sarilumab in severe SARS-CoV-2-related pneumonia. Methods 53 patients with SARS-CoV-2 severe pneumonia received intravenous Sarilumab; pulmonary function improvement or Intensive Care Unit (ICU) admission rate in medical wards, live disch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 24 publications
2
48
0
2
Order By: Relevance
“…In an early clinical study, siltuximab therapy at the onset of mechanical ventilation was associated with reduced occurrence of respiratory failure and death in severe COVID-19 cases (Gritti et al, 2020). Sarilumab is another IL-6R inhibitor that appears to be a potential therapy against severe COVID-19 (Gremese et al, 2020).…”
Section: Il-6 Inhibitorsmentioning
confidence: 99%
“…In an early clinical study, siltuximab therapy at the onset of mechanical ventilation was associated with reduced occurrence of respiratory failure and death in severe COVID-19 cases (Gritti et al, 2020). Sarilumab is another IL-6R inhibitor that appears to be a potential therapy against severe COVID-19 (Gremese et al, 2020).…”
Section: Il-6 Inhibitorsmentioning
confidence: 99%
“…It was observed that Tocilizumab was associated with a low death rate [ 162 ]. A study in severe COVID-19 pneumonia patients showed that treatment with Sarilumab exhibited promising results [ 163 ].…”
Section: Available Repurposed Drugs Against Covid-19mentioning
confidence: 99%
“…It shares the same mode of action as the previously described tocilizumab but binds the IL-6 receptor with higher affinity [ 86 ]. Gremese et al showed a trend of sarilumab to improve the clinical outcome in severe cases of COVID-19, compared to SOC-treated patients, albeit with only 53 participants in the study [ 87 ]. This result was supported by other early studies with limited patients numbers, which suggested that sarilumab-mediated IL-6 reduction correlated with faster recovery [ 88 , 89 , 90 ].…”
Section: Clinical-stage Therapeuticsmentioning
confidence: 99%